2019
DOI: 10.1002/psp.2287
|View full text |Cite
|
Sign up to set email alerts
|

Reunifying and separating: An analysis of residential arrangements of migrant couples in Ouagadougou, Burkina Faso

Abstract: This paper offers new evidence on the residential arrangements of couples in the context of migration and urbanisation in Africa, focusing on the case of Ouagadougou, Burkina Faso's capital city. We use a mixed-methods approach, combining data from a survey on the family histories of migrants merged with data from the Ouagadougou Health and Demographic Surveillance System and qualitative interviews. The objective is to analyse how the migrants themselves perceive "living apart together", the extent of this phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
3
0
3
Order By: Relevance
“…Bilecen and Sienkiewicz (2015) provide a strong example of using interviews to generate quantitative and qualitative social network material to study transnational migrant networks but do not address key epistemological questions of representation. Flahaux et al (2019) can be recommended as an example of conversation between data with different epistemological underpinnings (primary surveys with administrative data and interviews) at both data collection and analysis stages. The strength of their arguments about the experiences of migrants living apart would have been greater with reflection on how this mixed method approach added to this knowledge.…”
Section: Mixed Methods Population Geographymentioning
confidence: 99%
“…Bilecen and Sienkiewicz (2015) provide a strong example of using interviews to generate quantitative and qualitative social network material to study transnational migrant networks but do not address key epistemological questions of representation. Flahaux et al (2019) can be recommended as an example of conversation between data with different epistemological underpinnings (primary surveys with administrative data and interviews) at both data collection and analysis stages. The strength of their arguments about the experiences of migrants living apart would have been greater with reflection on how this mixed method approach added to this knowledge.…”
Section: Mixed Methods Population Geographymentioning
confidence: 99%
“…Spousal separation, marriage, and fertility are closely related events since the likelihood of a couple's residential separation is highest during the early years of marriage when family formation activities are most intense in the Mexico-United States migration context (Gupta 2002). In Ouagadougou, recently married couples are more likely to experience physical separation (Flahaux et al 2019). Marriage could also be an intermediary event between migration and fertility, such as in Kyrgyzstan (Hoem and Nedoluzhko 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous literature has showed that living together is perceived as an obligation in Burkina Faso (Flahaux et al 2019) and that women's long-distance commuting harms family stability in Germany (Kley and Feldhaus 2018). The persistency of spousal separation is variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estos nexos sirven particularmente para la movilidad y el proceso adaptativo. Por tanto, la experiencia migratoria se ve moldeada por el eje social en general y el familiar en particular (Flahaux et al, 2019;Herman, 2006). Algunas investigaciones se han centrado en la reconfiguración de familias transnacionales y en las parejas afectadas por la migración, sin embargo, terrenos fundamentales como la dimensión afectiva y sexual, siguen inexplorados (Birman y Bray, 2017;Flahaux et al, 2019;Martínez, 2018).…”
Section: Introductionunclassified
“…Por tanto, la experiencia migratoria se ve moldeada por el eje social en general y el familiar en particular (Flahaux et al, 2019;Herman, 2006). Algunas investigaciones se han centrado en la reconfiguración de familias transnacionales y en las parejas afectadas por la migración, sin embargo, terrenos fundamentales como la dimensión afectiva y sexual, siguen inexplorados (Birman y Bray, 2017;Flahaux et al, 2019;Martínez, 2018). En estas perspectivas emergentes sobre la experiencia sensible, los cambios y la permanencia de los grupos familiares y las parejas, se ha empleado la metodología cualitativa con el fin de explorar los discursos sobre las vivencias, opiniones, prácticas, rituales, emociones y otros elementos que están presentes en su cotidianidad.…”
Section: Introductionunclassified